SINTESIS BIODIESEL DARI MINYAK DEDAK PADI DENGAN KATALIS PADAT DARI LIMBAH PENGOLAHAN BAUKSIT (RED MUD) - Arif Hidayat; Yosef Budiman; Maharani Fatimah Azzahra; Tsabita Yamna Putri R. (Jurnal Inovasi Teknik Kimia, 2024)
Red mud, a solid waste from extraction process of bauxite mineral in Alumina Industry, was utilized as a solid catalyst for biodiesel production from rice bran oil. Red mud catalyst was prepared at calcination temperature of 800 °C and calcination time of 4 hours. The performance of this catalyst will be evaluated in terms of molar ratio of oil to methanol to, reaction temperature, and catalyst concentration. The results show that biodiesel yield is increasing by increasing molar ratio of methanol to oil, reaction temperature and catalyst concentration. The optimum reaction conditions were obtained at 65 C of reaction temperature, 1:12 of oil to methanol molar ratio, and 10% of catalyst amount. The highest biodiesel yield of 85% was obtained. Red mud catalyst has potential as an effective and economic viability as heterogeneous catalyst for biodiesel production, while offering a solution in the sustainable utilization of industrial waste.